Eskplorasi kesalahan siswa kelas VIII dalam menyelesaikan soal high order thinking skills pada materi luas segiempat - Muhamad Hanafi; Syamsuri Syamsuri; Anwar Mutaqin (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2022)
The difficulties experienced by students can cause errors in solving problems. Students' mistakes in obtaining the right solution in learning mathematics are important to be corrected to improve students' high order thinking skills. One of the basic competencies that students must have in quadrilateral material is solving contextual problems related to the area and perimeter of a quadrilateral. A total of 9 students were used as research subjects because they had consistent response and interview data. Errors made by students in solving HOTS questions based on Newman in this study were writing errors Encoding Error and process Skill Error. The factors that cause students to make mistakes in solving the HOTS questions on the area of a quadrilateral are carelessness, concepts, interests, and the quality of the teacher.